The Influence of Labor, Market Orientation, and Financial Literacy on the Performance of MSMEs - Ni Kadek Sintia Wati; Surya Dewi Rustariyuni (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital and fundamental role in driving Indonesia’s economy. Despite their importance, MSMEs continue to face various obstacles and challenges that negatively impact their performance. This study aims to examine the simultaneous and partial effects of labor, market orientation, and financial literacy on the performance of MSMEs. The sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression. The sample consisted of 125 MSME actors. The results indicate that labor, market orientation, and financial literacy simultaneously influence the performance of MSMEs in Denpasar City. Furthermore, labor, market orientation, and financial literacy each have a positive and significant partial effect on MSME performance. The implication of this research is that improvements in labor quality, market orientation, and financial literacy can enhance the performance of MSMEs in Denpasar City.